Utilization of Lemna minor as an Ammonia Phytoremediator at Kampoeng Pintar Oase Surabaya - Nursheila, Yasmine Artika; Fitrihidajati, Herlina; Candra, Adi; Nurcholis, Nurcholis; Aseyan, Aseyan (Universitas Muhammadiyah Malang, 2026)
Increasing food demand and high land use activities have led to the conversion of fisheries and agricultural areas. Kampoeng Pintar Oase Surabaya uses budikdamber (fish farming in buckets) as an alternative solution for small areas. Budikdamber produce ammonia from food waste and fish feces which can reduce water quality requiring environmentally friendly ammonia management solutions. This study aims to describe the effect of Lemna minor on ammonia reduction in budikdamber systems, the lowest ammonia level achieved after Lemna minor addition, the impact of ammonia reduction on catfish growth, and to assess the application of Lemna minor in budikdamber systems in supporting the achievement of SDG 2. The research was conducted in two stages. The first stage involved the creation of a pond culture medium using the observation method. The second stage was experimental, involving the implementation of pond culture for 21 days using two treatments, namely a control (without Lemna minor) and a treatment with the addition of Lemna minor, each of which was repeated three times. The parameters measured included ammonia levels, total nitrogen, pH, temperature, and DO. Data analysis was performed descriptively and quantitatively by testing ammonia and total nitrogen levels at BSPJI Surabaya based on the SNI 6484.4:2014 water quality standards. The results showed that the addition of Lemna minor reduced ammonia levels lower than the control treatment. The lowest ammonia level achieved was 0.72 mg/L on the 7th day. The best catfish growth was observed in the Lemna minor treatment with an average weight of 46 grams. Lemna minor is effective as an ammonia phytoremediator and supports fish growth in fish farming in buckets, as well as supporting the achievement of SDG 2 “Zero Hunger” through strengthening sustainable food security.